Hubungan Motivasi Dengan Keaktifan Ibu Membawa Balita Ke Posyandu Di Kelurahan Tonatan Kecamatan Ponorogo Kabupaten Ponorogo. - Sumini Sumini (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2014)
Motivation is a state that encourages the person to indulge in achieving goals. One of the factors which influencing liveliness of toddler to Posyandu is the maternal motivation. From the preliminary study showed 60.58% rate of mother-to-posyandu activity and targets that should be achieved is 85% toddler visits to neighborhood health center from 2011-2012. His can be caused by many mothers of toddlers who are less aware or weigh the importance of bringing their babies to Posyandu. The purpose of this study to determine the relationship of motivation with liveliness mothers bring infants to the Posyandu in the Village District Tonatan Ponorogo Ponorogo.Quantitative research with correlation studies. The population in this study were all mothers of children aged 0-5 years had as many as 307 in the neighborhood health center in the village Tonatan district Ponorogo with Simple Random Sampling technique, and the number of samples used by 76 respondents. The experiment was conducted on the second Friday in May 2013. The variables studied were maternal motivation (independent) and Motivation to toddler Mom Takes Posyandu (dependent). Methods of data collection using questionnaire instruments and KMS. To analyze the relationship between two variables using a statistical test Chi Square Test.Based on the results of the study showed that the majority of mothers infants (55.3%) had a positive motivation to come to the neighborhood health center, and the most active mom comes to neighborhood health center (65.8%). Based on Chi Square statistical test showed p = 0.034 with a significance level of 5%, so 0.034 <0.05 then H1 is accepted means that there is a relationship with the mother's motivation liveliness mothers carrying toddlers to posyandu and the low level of the relationship with the contingency coefficient value of 0.237.Active mothers are expected to come to the Posyandu to obtain counseling or routine weighing to monitor their children's growth, although not in the months giving Vitamin A. Nurse or midwife should conduct a home visit (home care) to foster community interest with posyandu activities.